DISC1 Regulates the Proliferation and Migration of Mouse Neural Stem/Progenitor Cells through Pax5, Sox2, Dll1 and Neurog2 - Wu, Qian; Tang, Weiting; Luo, Zhaohui; Li, Yi; Shu, Yi; Yue, Zongwei; Xiao, Bo; Feng, Li (Frontiers in Cellular Neuroscience, 2017)
Background: Disrupted-in-schizophrenia 1 (DISC1) regulates neurogenesis and is a genetic risk factor for major psychiatric disorders. However, how DISC1 dysfunction affects neurogenesis and cell cycle progression at the molecular level is still unknown. Here, we investigated the role of DISC1 in regulating proliferation, migration, cell cycle progression, and apoptosis in mouse neural stem/progenitor cells (MNSPCs) in vitro. Methods: MNSPCs were isolated and cultured from mouse fetal hippocampi. Retroviral vectors or siRNAs were used to manipulate DISC1 expression in MNSPCs. Proliferation, migration, cell cycle progression, and apoptosis of altered MNSPCs were analyzed in cell proliferation assays (MTS), transwell system, and flow cytometry. A neurogenesis specific PCR array was used to identify genes downstream of DISC1, and functional analysis was performed through transfection of expression plasmids and siRNAs. Results: Loss of DISC1 reduced proliferation and migration of MNSPCs, while an increase in DISC1 led to increased proliferation and migration. Meanwhile, an increase in the proportion of cells in G0/G1 phase was concomitant with reduced levels of DISC1, but significant changes were not observed in the number MNSPCs undergoing apoptosis. Pax5, Sox2, Dll1 and Neurog2 emerged as candidate molecules downstream of DISC1, and rescue experiments demonstrated that increased or decreased expression of either molecule regulated proliferation and migration in DISC1-altered MNSPCs. Conclusions: These results suggest that Pax5, Sox2, Dll1, and Neurog2 mediate DISC1 activity in MNSPC proliferation and migration.